Money minded families : how to raise financially well children - Mackara, Stephanie (John Wiley & Sons, 2020)
"Money is always a concern regardless of background or standing in society. Every adult and child needs to become "financially well," able to align their personal values with their finances to they may save, spend, share, and invest their money with purpose, and for a sound financial future. The book teaches: Holistic guidance for families to learn to live their best financial lives, instead of just getting by Financial mindfulness, Values-oriented spending, Healthy financial socialization, Key financial concepts. Members of today's young adult generation often find themselves saddled with debt and unprepared to manage their day-to-day finances. The topic of financial independence has a strong following among millennials, and many are just learning in their late 20s and 30s how to get ahead financially. As they raise families, the seek guidance to raise financially well children. The next generation needs to be better prepared to live financially well lives"--